2021
DOI: 10.1186/s12885-021-08207-7
|View full text |Cite
|
Sign up to set email alerts
|

Five long non-coding RNAs establish a prognostic nomogram and construct a competing endogenous RNA network in the progression of non-small cell lung cancer

Abstract: Background Accumulating evidence has revealed that long non-coding RNAs (lncRNAs) play vital roles in the progression of non-small cell lung cancer (NSCLC). But the relationship between lncRNAs and survival outcome of NSCLC remains to be explored. Therefore, we attempt to figure out their survival roles and molecular connection in NSCLC. Methods By analyzing the transcriptome profiling of NSCLC from TCGA databases, we divided patients into three gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
5
1
Order By: Relevance
“…Generally, the nomogram exerted a medium accuracy on predicting OS of LUSC, displaying a better overall net benefit than the T, N stating system for predicting 1- and 3-year OS rate. Although in terms of validity, this ATIRE-based nomogram did not display a superior performance compared to previously published gene-expression-based nomograms as shown by the Harrell’s C-indexes, given an amount of gene-expression-based nomograms exerted Harrell’s C-indexes ranging from 0.65–0.85 [ 44 49 ]. However, in terms of determination reliability, quantification of AITRE level is more stable and reliable than that of gene expression.…”
Section: Discussioncontrasting
confidence: 66%
“…Generally, the nomogram exerted a medium accuracy on predicting OS of LUSC, displaying a better overall net benefit than the T, N stating system for predicting 1- and 3-year OS rate. Although in terms of validity, this ATIRE-based nomogram did not display a superior performance compared to previously published gene-expression-based nomograms as shown by the Harrell’s C-indexes, given an amount of gene-expression-based nomograms exerted Harrell’s C-indexes ranging from 0.65–0.85 [ 44 49 ]. However, in terms of determination reliability, quantification of AITRE level is more stable and reliable than that of gene expression.…”
Section: Discussioncontrasting
confidence: 66%
“…In the previous studies, Yu et al identified five lncRNAs which showed important prognostic values in NSCLC. LINC01833 showed the most significant upregulation in the NSCLC tissues compared with control group [ 17 ]. The present study shows that overexpression of LINC01833 promoted cell proliferative, invasive, and migratory capabilities, inhibited cell apoptosis, and promoted tumorigenesis, suggesting that LINC01833 can promote NSCLC progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several lncRNAs were revealed as important biomarkers in NSCLC [ 13 , 14 ], such as long intergenic non-protein coding RNA 504 and long intergenic non-protein coding RNA 691 [ 15 , 16 ]. Recently, Yu et al successfully identified five survival-related lncRNAs using transcriptome profiling analysis of NSCLC from TCGA database [ 17 ]. Among them, the expression of long intergenic non-protein coding RNA 1833 (LINC01833) showed the most significant upregulation in tumors compared with normal group, suggesting that LINC01833 might act as an oncogene in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…And, many studies have carried out a comprehensive analysis of ncRNA and its related co-expression and ceRNA network differential expression profiles in NSCLC. Yu and Ren (2021) constructed a ceRNA network by analyzing the differentially expressed lncRNAs of NSCLC transcriptome profiling from TCGA. The network can effectively predict the overall survival of NSCLC and may guide the treatment of NSCLC.…”
Section: Discussionmentioning
confidence: 99%